2024
DOI: 10.3390/jfmk9010042
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effect of Dynamic vs. Proprioceptive Neuromuscular Facilitation Stretching on Sprint and Jump Performance

Nor Fazila Abd Malek,
Ali Md Nadzalan,
Kevin Tan
et al.

Abstract: Participating in sports has been shown to promote overall wellness and, at the same time, reduce health risks. As more people are participating in sports, competitions have increased, and every aspect of the game has been focused by coaches and athletes in order to improve performance. One of these aspects is the warm-up session. The purpose of this study was to investigate the acute effect of a dynamic warm-up versus a proprioceptive neuromuscular facilitation (PNF) warm-up on the sprint and jump performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Accelaration is the first 10 meters of sprinting activity (Hewit et al, 2011;Little, 2005. ) In addition, research using other methods to increase eccentric hamstring strength has indeed reported improvements in jump and sprint performance (de Hoyo et al, 2015;Malek et al, 2024). Jumping ability has also been associated with sprinting performance (Wisloff et al, 2004, Kukric et al, 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Accelaration is the first 10 meters of sprinting activity (Hewit et al, 2011;Little, 2005. ) In addition, research using other methods to increase eccentric hamstring strength has indeed reported improvements in jump and sprint performance (de Hoyo et al, 2015;Malek et al, 2024). Jumping ability has also been associated with sprinting performance (Wisloff et al, 2004, Kukric et al, 2022.…”
Section: Introductionmentioning
confidence: 99%